ANALISIS STRATEGI PENGEMBANGAN USAHA DENGAN PENDEKATAN BUSINESS MODEL CANVAS - Yudha, Mellisa Magdalena; Mariam, Iis; Rosalina, Erlyn (Transpublika Publisher, 2023)
The aim of this research is to analyze the business model of X Grilled Chicken Restaurant in Depok and design a new business model using the Business Model Canvas approach. This research uses the Sequential Exploratory model research method, which consists of qualitative methods as the main method and quantitative as an additional method. Data were collected through interviews, observation, documentation, questionnaires, and triangulation. To describe the current business model, the Business Model Canvas (BMC) method was used, while to formulate alternative strategies, Strength, Weakness, Opportunity, Threat (SWOT) analysis was used. To determine the priority of alternative strategies, the Quantitative Strategic Planning Matrix (QSPM) was used. The results of the SWOT Analysis resulted in eight alternative strategies, including focusing on Value as fnb tech, continuous digital market research, evaluation of marketing strategies, expansion of business relationships, more attractive promotions, adding new employees, increasing the allocation of marketing costs, and making stricter rules for employees who violate SOPs. Based on the results of the QSPM Matrix calculation, the strategy of continuous digital market research is the highest priority with a value of 13.87.